BANTUAN OPERASIONAL MANAJEMEN PELAKSANAAN PENDIDIKAN ANAK DINI - Muryadi Muryadi (Universitas Muhammadiyah Kotabumi, 2021)
A legal analysis of the Operational Assistance for the Implementation of Early Childhood Education (BOP PAUD) at Aisyiyah Bustanul Athfal Kindergarten, Bandar Putih Tua village, Anak Ratu Aji sub-district, Central Lampung district in 2020/2021 was conducted to determine whether the implementation process was in accordance with the Ministry of Education and Culture's (PERMENDIKBUD) Number 20 of 2020 concerning amendments to the Regulatio Using a problem-solving strategy The research in this study employs an Empirical Approach, which entails gathering data and conducting direct field research to obtain clearer and more accurate data about the issues being addressed in the study.The analysis of the Implementation of Operational Assistance for the Implementation of Early Childhood Education (BOP PAUD) was carried out by focusing on the procurement of preventive goods from the Covid-19 Virus, as well as the process of reporting accountability for the use of BOP PAUD funds by carrying out accountability, according to the study's findings.the solution to the utilization of funds from the receipt and distribution procedure